The research progress of targeted therapy in acute myeloid leukemia based on bibliometric analysis - Huang, Wanxue; Sun, Gongrui; Wang, Qi; Long, Zhiguo (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a malignant proliferative clonal disease, characterized by a wide spectrum of molecular alterations. Although targeted therapy for AML has resulted in pronounced achievements in the past decade, clinical resistance caused by mutations in targeted oncogenes has been observed. A subset of patients with AML still requires the treatment of refractory and relapsed diseases. The field of targeted therapy in AML still presents many challenges. More studies are needed to overcome those obstacles. Through the CiteSpace tool, we can gain a systematic understanding of the current achievements in targeted therapy in AML and we can predict hot research topics. Relevant publications from the Web of Science Core Collection (WoSCC) were retrieved and the acquired data was analyzed by CiteSpace to identify and predict trends and research hotspots in this field. We found that research on AML had focused on venetoclax resistance, novel therapies (such as targeting epigenetic modification), and FLT3 mutation in the past decade. The clustering of keywords suggested interest in cell-targeted therapy (CAR-T, natural killer cells), signaling pathways (mTORC1), epigenetic therapies, and leukemic stem cells (LSCs). Drug resistance causing failure and relapse of treatment has raised increasing concern and LSCs play a key role in relapsed AML, which represent an important direction for identifying targets for AML treatment in the future.